A procedural framework for extension of time (EoT) claim settlement in the Malaysian construction industry / Norazian Mohamad Yusuwan - Mohamad Yusuwan, Norazian (2016)
The construction industry is often burdened by various problems associated with contractual claims that affect not only the administration and management of projects but also disrupt the smooth running of construction activities as well as contribute to the occurrence of disputes between the parties involved. Such disputes will affect harmonious relationships among industry players if they are not tackled in the best possible way. Despite the many studies that have been carried out with regard to improving the management of contract claims, yet very little research has been conducted to address the issue in relation to the extension of time (EoT) claim, specifically as to what constitutes a good EoT claim and the possible measures that can be taken by industry players towards the successful settlement of an EoT claim. Therefore, this study was undertaken with the aim of developing an appropriate framework that can help the parties involved in the construction industry to come up with EoT claims that can be resolved harmoniously without any unnecessary disputes. Prior to the development of such a framework, the practices of industry players in dealing with EoT claims were investigated, contentious issues in relation to EoT claims and the reasons for the rejection of such claims were revealed, and the success elements for EoT claims and initiatives to reduce the likelihood of failure of such claims were identified. The triangulation method comprised of a questionnaire survey, semi-structured interviews and a modified Delphi approach, was employed to achieve the research objectives. Such an approach will produce a robust and reliable data. The findings revealed that weaknesses in terms of the management and keeping of records as well as the lack of competency in handling claims which result in the submission of poor and incomplete claim documents are among the factors that disrupt the preparation and assessment of EoT claims, which may then lead to a rejection of such claims. On the other hand, issues associated with EoT claims that often create dissatisfaction and conflict between the parties involved are concurrent delays, eligibility of time extension claims, non-compliance with contract requirements, inadequate efforts to mitigate delays, and also the permissible time period for extensions. The conservation of harmonious business relationships, the preservation of reputation as well as continuity in the construction industry are seen as the major factors influencing the likelihood of industry practitioners opting for negotiations as a medium to resolve any problems and disputes in relation to EoT claims. The findings from the research were then used to develop a framework for a successful EoT claim which contained elements that contribute to the success of EoT claims and initiatives that can be implemented in order for claims to be successful, and to reduce the possibility of failure of such claims. Subsequently, a personal (face-to-face) questionnaire survey conducted with eleven (11) experts from the industry confirmed that the framework is appropriate and is viewed as having great potential for implementation in the construction industry in Malaysia. The findings of this research may offer valuable information, not only to industry players but also to students in the related fields, in preparing themselves to face the challenges of working in the construction industry.